Administrative regulation of land relations in Ukraine - Шуст, Анна Петровна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article is devoted to ensuring the mechanism of legal regulation of land relations in Ukraine. It is determined that the mechanism of legal regulation is an integral part of the development of society, objectively inherent in development, accompanies it, providing a regulated character with the help of individual components (parts). These features of the mechanism of legal regulation are identified through the main stages of the legal regulation mechanism. It is concluded that the Constitution of Ukraine, in the form of general principles, enshrined constitutional provisions on land that created the basis for sectoral land legislation, namely: defined the special position of the land as the main national wealth, defined the land as an object of private, communal and state property, provided for cases Termination of this right, and also introduced the principle of special protection of land by the state. These fundamental provisions, which found their consolidation at the constitutional level, became the basis for the adoption of appropriate land legislation. Thus, having analyzed different approaches to determining the structure of the mechanism of legal regulation, it can be concluded that legal regulation consists of such stages: A) the formation and enforcement of the norms of law that govern certain social relations; B) the emergence of subjective rights and obligations (specific legal relations); C) the realization of rights and duties, that is, the norms of law. In addition, some scholars also provide additional optional stages such as the use of the rules of law and their interpretation. At the same time, legal instruments are elements of the legal regulation mechanism: legal norms, legal facts, legal relations, acts of implementation of subjective rights and obligations, acts of using the norms of law, acts of interpretation of the norms of law. The last two elements are optional and are used only in cases of need.